Dysregulation of CDX1, CDX2 and SOX2 in patients with gastric cancer also affects the non-malignant mucosa. Issue 9 (23rd April 2013) - Bornschein, Jan; Tóth, Kinga; Selgrad, Michael; Kuester, Doerthe; Wex, Thomas; Molnár, Béla; Tulassay, Zsolt; Malfertheiner, Peter
Abstract : The interplay between gastric and intestinal transcription factors has an important impact on gastric carcinogenesis. We compared the gene expression of CDX1, CDX2, SOX2 and related downstream genes in tumour and tumour surrounding gastric tissue of 48 gastric cancer patients with 30 healthy controls. There was no difference of gene expression of CDX1 and CDX2 between tumour or tumour-adjacent and tumour-distant mucosa, but both factors were significantly higher expressed in cancer patients compared with controls (p<0.01). SOX2 was downregulated in tumour tissue compared to controls, whereas tumour-adjacent and tumour-distant mucosa showed intermediate SOX2 expression. Laurén type and Helicobacter pylori infection had no significant impact on expression of the transcription factors. Expression of CDX1 and CDX2 was higher in the presence of intestinal metaplasia. The differential regulation of the gene expression of CDX1, CDX2 and SOX2 in patients with gastric cancer affects not only the tumour but also the non-neoplastic tumour-distant mucosa.